Distribution of constitutive heterochromatin in Pachycoris torridus (Hemiptera, Scutelleridae) with different chromatic patterns - Souza-Firmino, T. S. [UNESP]; Alevi, K. C. C. [UNESP]; Pereira, L. L. V. [UNESP]; Souza, E. R. S. [UNESP]; Junior, F. C. S. [UNESP]; Banho, C. A. [UNESP]; Carmo, G. O. [UNESP]; Itoyama, M. M. [UNESP] (Funpec-editora, 2015)
The stink bug Pachycoris torridus is a pest of great agricultural importance due to its records on culture of physic nut (Jatropha curcas), which is the raw material for biodiesel production. An interesting feature of this insect is its high phenotypic variability, a characteristic that resulted in it being classified as a new species on eight separate occasions. In the suborder Heteroptera, the heterochromatin pattern is specific and often allows species to be differentiated. To confirm whether there is differentiation between specimens of P. torridus with different color patterns (yellow, orange, brown, and red), samples were analyzed cytogenetically using the C-banding method. During meiotic prophase, the four color patterns analyzed showed a large heterochromatic chromocenter, consisting of a combination of both sex chromosomes (X and Y). Thus, the present study reports chromosomal homogeneity in different color patterns of P. torridus and highlights the importance of this tool in the description of new species.
Keywords: Heteroptera; Spermatogenesis; Chromosomal homogeneity; Meiosis